Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms 2009
DOI: 10.1137/1.9781611973068.9
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Biased Lattice Configurations using Exponential Metrics

Abstract: Monotonic surfaces spanning finite regions of Z d arise in many contexts, including DNA-based self-assembly, card-shuffling and lozenge tilings. We explore how we can sample these surfaces when the distribution is biased to favor higher surfaces. We show that a natural local chain is rapidly mixing with any bias for regions in Z 2 , and for bias λ > d 2 in Z d , when d > 2. Moreover, our bounds on the mixing time are optimal on d-dimensional hyper-cubic regions. The proof uses a geometric distance function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 13 publications
(27 reference statements)
2
55
0
Order By: Relevance
“…They relate this biased shuffling Markov chain to a chain on an asymmetric simple exclusion process (ASEP) and showed that they both converge in Θ(n 2 ) time. These bounds were matched by Greenberg et al [10] who also generalized the result on ASEPs to sampling biased surfaces in two and higher dimensions in optimal Θ(n d ) time. Note that when the bias is a constant for all i < j there are other methods for sampling from the stationary distribution, but studying the Markov chain M nn is of independent interest, partly because of the connection to ASEPs and other combinatorial structures.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…They relate this biased shuffling Markov chain to a chain on an asymmetric simple exclusion process (ASEP) and showed that they both converge in Θ(n 2 ) time. These bounds were matched by Greenberg et al [10] who also generalized the result on ASEPs to sampling biased surfaces in two and higher dimensions in optimal Θ(n d ) time. Note that when the bias is a constant for all i < j there are other methods for sampling from the stationary distribution, but studying the Markov chain M nn is of independent interest, partly because of the connection to ASEPs and other combinatorial structures.…”
Section: Introductionmentioning
confidence: 69%
“…We use a mapping from biased permutations to multiple particle ASEP configurations with n zeros and n ones. The resulting ASEPs are in bijection with staircase walks [10], which are sequences of n ones and n zeros, that correspond to paths on the Cartesian lattice from (0, n) to (n, 0), where each 1 represents a step to the right and each 0 represents a step down (see Figure 1b). In [10], Greenberg et al examined the Markov chain which attempts to swap a neighboring (0, 1) pair, which essentially adds or removes a unit square from the region below the walk, with probability depending on the position of that unit square.…”
Section: A Positively Biased P That Is Slowly Mixingmentioning
confidence: 99%
See 3 more Smart Citations